IMPLEMENTASI MODEL MODIFIKASI KURIKULUM SEKOLAH INKLUSI BERDASARKAN KEBUTUHAN INDIVIDU PESERTA DIDIK - Anggun Prima Handari; Opi Andriani; Wuzira Azka Nadya (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The curriculum used by the Muara Bungo State Special School, which is a special school, is the National Curriculum for ABK students, which has been modified for its implementation. This research method is descriptive qualitative. Data was collected through interviews, observation and documentation. The aim of the research is to find out how curriculum modifications are implemented at the Muara Bungo State SLB. The results of this research show that the implementation of curriculum modifications is presented in the form of an Individual Learning Program (PPI) and the implementation of curriculum modifications is carried out in stages per semester according to the achievements of each student. The implementation of curriculum modifications also involves the school principal to direct and special accompanying teachers as teachers who Responsible for students with special needs. The purpose of this curriculum modification is to make it easier for students to carry out the learning process in accordance with their needs and abilities. The development of social skills at Muara Bungo State SLB is good. The visible results in the development of social skills are the attitude of students with special needs who are more open to the surrounding environment, they can get to know each other and greet each other, both the teacher, the principal and their peers and the student's personality can be handled well. Special accompanying teachers always train students with special needs in socializing by playing with friends, giving permission to borrow items from friends or from teachers or school principals. Implementation of Curriculum Modifications in efforts to develop social skills at the Muara Bungo State Special School is carried out in stages according to the development of each student, to improve social skills it is carried out by providing activities in the form of togetherness activities carried out on Mondays for ceremonial activities and Fridays for gymnastics activities.